'Cognitive enhancers': A qualitative exploration of university students' experiences with prescription medicines for academic purposes. Issue 7 (1st October 2022) - Monnet, Fanny; Ergler, Christina; Pilot, Eva; Sushama, Preeti; Green, James
Qualitative work with students who use prescription medicines for academic purposes is limited. Thus, a more nuanced understanding of tertiary students' experiences is urgently needed. Our study – which draws on five semi-structured interviews with New Zealand university students, complemented with information from local newspapers, blog entries and discussion forums – reveals students' motivations and perceived effects, their risk perceptions and provides insights into the circumstances enabling the engagement with prescription medicines for academic purposes. Students were influenced by peers and social norms; and ideas about identity, morality and fairness also played a role for engaging with cognitive enhancers. Students used high levels of stress and workload to justify their use but took individual responsibility for their practices. By taking responsibility in this way, rather than considering it as a product of their environment, they buy into the neoliberal university discourse. Unexpectedly, some participants were already receiving medically justified psychopharmacological treatment but extended and supplemented this with nonmedical use. Others considered their use as being for academic emergencies, and that their low level of use helped manage risks. Overall, students viewed pharmacological cognitive enhancement for improving academic performance as cautious, safe, and morally acceptable. We argue in this paper that a local understanding of students' motivations, justifications and perceptions of pharmacological cognitive enhancement is required, to tailor policies and support systems better to their needs and behaviours.